Body schema(tism) and the logos of life: a phenomenological reconsideration - Butnaru, Denisa (Investigaciones Fenomenológicas, 2014)
Body image and body schema are two phenomenological concepts which generated a revival of Maurice Merleau-Ponty’s philosophical heritage. In the present text I intend to inquire on the relation between these two concepts and that of Logos of life, another challenging point in the Merleau-Pontyan thought. In order to delineate the correlation between body schema, body image and my understanding of a logic of life, I will first explore how what I term “schematism of the body” is connected to an inherent model of life and living and how this schematism is reflected in the body image. I will turn further to the relation between body and world and highlight how the life of the body defines itself as meaningful in the context of both the surrounding world (Umwelt) and the lifeworld (Lebenswelt). In a third part of my analysis I shall point out how the relation between body schematism and motile intentionality redefines corporeal inten-tionality. I shall conclude by noting the role of the Logos of life, through which corporeity, in its position of meaning project, is instituted as body schematism. Los conceptos fenomenológicos de imagen corporal y esquema corporal han dado lugar a un resurgimiento del legado filosófico de Maurice Merleau-Ponty. En este texto pretendo investigar la relación entre estos dos conceptos y el de Logos de la vida, otro elemento estimulante del pensamiento Merleau-Pontiano. Con el fin de trazar la correlación entre es-quema corporal, imagen corporal y mi interpretación de la lógica de la vida, exploraré en pri-mer lugar cómo el término “esquematismo del cuerpo” está conectado con un modelo inheren-te de vida y de vivir, y cómo este esquematis-mo se refleja en la imagen corporal. Consideraré después la relación entre cuerpo y mundo y remarcaré cómo la vida del cuerpo se define como significativa en el contexto tanto del mundo circundante (Umwelt) como del mundo de la vida (Lebenswelt). En la tercera parte de mi análisis señalaré cómo la relación entre esquematismo corporal e intencionalidad moto-ra redefine la intencionalidad corporal. Concluiré destacando el papel del Logos de la vida, a través del cual la corporeidad, en su posición de proyecto significativo, se instituye como esquematismo corpora